Changes in Serum Enzymes and Related Mechanisms of Respiratory Dysfunction in Patients after Venomous Snake Bite and Analysis of Anti-Venomous Snake Serum Treatment: Changes in Serum Enzymes after Venomous Snake Bite - Nong, Jifei; Huang, Zhou; Huang, Zhengzhuang; Yang, Jie; Li, Jincheng; Huang, Dongling; Wang, Wei (Cellular and Molecular Biology, 2022)
To explore the changes in serum enzymes in patients with a snake bite, the treatment of respiratory dysfunction, and the clinical effect of anti-snake serum treatment. Fifty snake bite patients admitted to the emergency medicine department were selected and rolled into a light group (n=27), heavy group (n=15), and critical group (n=8). Anti-venomous snake serum was injected intravenously. Patients with severe respiratory dysfunction were treated with mechanical ventilation. The white blood cell (WBC), C-reactive protein (CRP), interleukin-6 (IL-6), alanine aminotransferase (ALT), aspartate aminotransferase (AST), blood urea nitrogen (BUN), and creatinine (Cr) counts of the heavy group and the critical group were higher versus light group (P<0.05). The WBC, CRP, IL-6, ALT, AST, BUN, and Cr of the critical group were higher versus the heavy group (P<0.05). The prothrombin time (PT), activated partial thrombin time (APTT), and thrombin time (TT) of the heavy group and critical group were longer versus the light group (P<0.05). The PT, APTT, and TT of the critical group were longer than the heavy group (P<0.05). The fibrinogen (FIB) of the light group was higher in contrast to that in the other two groups (P<0.05), while the critical group was the lowest (P<0.05). In summary, the severity of snakebites in patients can be evaluated according to the indexes of WBC, IL-6, coagulation function, and liver and kidney function.